Real Time Continuous Monitoring of Cerebral Blood Flow Autoregulation using Near-Infrared Spectroscopy in Patients Undergoing Cardiopulmonary Bypass - Brady, Kenneth (Stroke, 2010)
BACKGROUND AND PURPOSE: Individualizing mean arterial blood pressure (MAP) targets to a patient’s cerebral blood flow (CBF) autoregulatory range might prevent brain ischemia for patients undergoing cardiopulmonary bypass (CPB). This study compares the accuracy of real-time CBF autoregulation monitoring using near infra-red spectroscopy (NIRS) with that of transcranial Doppler (TCD). METHODS: Sixty adult patients undergoing CPB had TCD monitoring of middle cerebral artery blood flow velocity (MCA-FV) and NIRS monitoring. The mean velocity index (Mx) was calculated as a moving, linear correlation coefficient between slow waves of MCA-FV and MAP. The cerebral oximetry index (COx) was calculated as a similar coefficient between slow waves of cerebral oximetry and MAP. When CBF is autoregulated, Mx and COx vary around zero. Loss of autoregulation results in progressively more positive Mx and COx. RESULTS: Mx and COx showed significant correlation (r=0.55, P<0.0001) and good agreement (bias, 0.08 ± 0.18, 95% limits of agreement: −0.27 to 0.43) during CPB. Autoregulation was disturbed in this cohort during CPB (average Mx 0.38,95% CI 0.34 to 0.43). The lower CBF autoregulatory threshold (defined as incremental increase in Mx > 0.45) during CPB ranged from 45 to 80 mmHg. CONCLUSIONS: CBF autoregulation can be monitored continuously with NIRS in adult patients undergoing CPB. Real-time autoregulation monitoring may have a role in preventing injurious hypotension during CPB.